Analisis strategi kompetitif PT. Bank Central Asia - Vaddhano, Nyana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
PT. Bank Central Asia is one of the leading companies in the Indonesian banking industry. Management's expertise in innovation and long-term planning is able to consolidate the company's position and create a competitive advantage. This research seeks to examine the competitive strategy of PT. Bank Central Asia is based on three established theories in strategic management science, namely Porter's Competitive Positioning, the Resource-Based View, and the Delta Model. The research method used in this study is a descriptive qualitative research analysis method. According to the findings of the study, the banking industry has collusive oligopoly competition and the status of PT. Bank Central Asia, as one of the leading companies, strengthens the bargaining power of PT. Bank Central Asia is in the banking industry. A culture of hospitality and respect for customers that is rooted in all company units as well as a culture of continuous innovation are internal competencies that lead to a company's competitive advantage. In order to keep consumers loyal to the company, P.T. Bank Central Asia prioritizes the massive distribution of ATM machines and the establishment of a comprehensive banking ecosystem for customers and companies.